The Role of The Leader's Communication Style on Substitutes in The Organization - Oktri Permata Lani; Mulyanti Syas; Nurjanah Nurjanah (IAIN Batusangkar, 2022)
In organizations that have a very important role in advancing the organization or making the setback of the organization is the leader. In every time and condition a leader must pay attention to how he must communicate, both verbal communications, namely speaking lisa, how to speak words and also how to communicate non-verbal that is seen from in terms of how to behave, behave, facial expressions, and body language when dealing with subordinates. The research method is descriptive qualitative. Communication can take place well if there is mutual understanding between the sender and receiver of the message, so there is an understanding of an idea or ideas. Through good understanding, the purpose of communication to provide stimulation for attitude changes will be easily achieved. The purpose of this study is to determine the role of the leadership style of communication towards subordinates in the organization, and to find out the obstacles of the role of the leadership style of communication to subordinates in the organization